Investigation of biotechnological processes of cultivation of lactic acid bacteria in the presence of dietary fiber from pumpkin seeds - Kylymenchuk, Olena; Konovka, Alla (Problems of Environmental Biotechnology, 2021)
Research of separate technological and biotechnological aspects, which are necessary for the development of the technology of obtaining metabolic probiotic, where as a prebiotic component and regulator of synthesis, dietary fibers from pumpkin seeds are used.